Child Labour in Pakistan - A tip of an iceberg - Zaidi, Nosheen; Javed, Najma; Khan, Muhammad Shoaib (Journal of Postgraduate Medical Institute, 2013)
Objectives: To study the basic demographic characteristics of child laborers and to ascertain their workingconditions Methodology: This cross sectional study was conducted in district Rawalpindi from January to September 2008and 700 children between 4 - 18 years were enrolled after taking informed consent from both children andtheir masters. Information on demography and work details was recorded on a structured performa. Results: Total 700 children 4-18 years old with mean age of 13.5 years were enrolled. Male:Female ratiowas 5.4:1. Most of the children (401) had a family size of 5-8 members. In 634 cases, 1-4 family memberswere earning while 05 had 10-12 earning members. Only 479 (68%) children ever attended school, mostly(291, 42%) till primary level. 258 children's families had monthly income of more than PKR 8000, 210PKR 6000-8000, 167 PKR 4000-5000 and 63 families were earning less than PKR 3000/ month. Mostly(270) worked in shops. Reason of work was low family income in 222 and poverty in 207 children. 283children worked for 7-10 hours per day, 216 for 07 days, 115 for 4-6 hours, 45 for more than 12 hoursand 39 for 1-3 hours. Maximum monthly pay was 1000- 2000 rupees in 187 and minimum 500 rupees permonth in 106 children. 284 cases sustained injury while at work. Conclusion: Most child labourers are male with a family size of 5-8 members, never attended any schooland living in a family whose monthly income is less than 8000 Pakistani Ruppee. The major reason ofwork was low family income and poverty.